(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Today the social media has became an integral part in people’s lives. Social media became more perceptible at higher education level and changing the ways students collaborate, learn and communicate. Students’ communication with faculty and peers over social networking sites can help a student in socializing, to find friends and discuss study related matters. Many scholars in their research studies had favored the usage of social media as an additional tool for education. There is abundance of educational content available online for the use of students. This problem of plenty has aroused the need for purposeful content a student seeks. In this paper, an effort has been made to identify influencing factors influencing students in education dissemination on social media. The data was collected from management students through Likert scale and analyzed using factor analysis with reliability and validation checks. The emerged factors that came out were topic discussion, better learning, motivating, and communicative shows the effectiveness of social media in education dissemination. This study will help higher education institutes and faculty in disseminating education over social media which will further help students in education.